The square against the ballot box: Bolsonaro supporters’ challenge to the Presidential Election in Rio de Janeiro (Antropolítica - Revista Contemporânea de Antropologia, 2024)
This article looks at the occupation of the square next to the army headquarters in Rio de Janeiro the day after the second round of Brazil’s 2022 presidential election. This mobilization brought together radical Bolsonarist voters and activists calling on the army to undo the election result to restore the defeated President, Jair Bolsonaro. This study provides insights into the dynamics of collective action in the radical fringes of Bolsonarism. While resorting to a non-violent repertoire of action, namely the occupation of a square, the participants borrowed from the conceptions and logics of action of military circles. The duality of this mobilization provides insight more generally into a central dimension of Bolsonarism, namely the mobilization of the rules of democracy and the rule of law to disqualify their foundations and procedures.